Implementation of Business Intelligence In Product Services A Banking (Case Study: PT Bank Sumsel Babel Baturaja Branch) - Wiradarma, Sekar Sari; Tania, Ken; Hardiyanti, Dinna Yunika (Jurnal Sistem Informasi, 2017)
Business Intelligence (BI) is a collection of theories, methodologies, processes, architectures, and technologies that convert raw data into quality information for business purposes. BI can handle a large amount of information that can help in identifying problems and developing new opportunities. In designing and implementing Business Intelligence (BI) concept for monitoring banking product service using reference business intelligence roadmap approach. Business intelligence roadmap is one example of BI development that can be emulated because of its agile and adaptive nature and is intended to support the development of BI. By utilizing Business Intelligence application on transaction history of banking product data, it is hoped able to produce information that can support in giving recommendation and decision making appropriately. The data and information generated also become more accessible and easier to understand (user friendly).   Keywords: business intelligence, business intelligence roadmap, OLAP, banking products